Leading for organisational change building purpose, motivation and belonging - Emery, Jennifer 1977- (Hoboken Wiley, 2019)
"Harness the seven key elements of successful organisational change Leading for Organisational Change is an intelligent and practical guide to the human side of merger integration and other organisational change. Building a clear sense of common purpose and then reinforcing it through storytelling can underpin the success of an integration or significant change programme. Pulling together the best thinking from neuroscience, psychology and business, and her rich personal experience in twenty years of leading change projects in professional services organisations and other people-centred businesses, author Jennifer Emery presents a framework for change rooted in seven key themes that help organisations establish their BECAUSE: belonging, evolution, confidence, agility, understanding, simplicity and energy. Exploring the role each theme plays in the context of change, this insightful and warm book shares real-world examples and provides advice on building purpose and culture and strengthening motivation through listening, empowering and collaborating. Clear understanding of purpose, powerful communication techniques and carefully planned implementation strategies assist in navigating an often stressful and uncertain period of change, and can even enable organisations to thrive throughout this period. This book encourages you to apply important lessons to your own context, allowing you to: Focus on the human, cultural and practical elements of organisational change Apply central concepts of communication and motivation to a wide array of situations in your personal and business life Understand perspectives on change from a broad range of professional sectors Build and strengthen communication skills to promote a sense of shared purpose Leading for Organisational Change offers a warm and intelligent perspective on the personal and inter-personal factors that contribute to successful integration. An invaluable resource for professional services and people-focused organisations, this book provides advice that can cross sectors and lend insight to any major change programme"--Publisher.
"Sales handles: -High-profile client list who CMS work with. CMS would buy and promote this book heavily within their own firm and with clients. Those CMS clients who also contributed to the book - and other contributors in the legal sector. -CMS have 200,000 client contacts in their CRM database, and 31,047 subscribers to their main newsletter/news service, LawNow. The book will be promoted to all of these contacts and newsletter subscribers. -In 2017, CMS sent out 1,500 articles and 50 other publications via Law-Now. All Law-Now content is also syndicated to Lexology which has in excess of 300,000 subscribers. Law-Now and Lexology will both be utilized by CMS to promote and market the new book. Market description: -The book will be particularly useful for anyone involved in merging and integrating businesses together and with an interest in making the newly merged business a success. Because it is written from an in-house perspective, it will resonate more with those who are a little bit in love with their businesses and the people in them, than with those who bring a more transactional perspective to bear. -This book will also be useful for coaches and HR professionals. -It may also be of interest to academics to those teaching or studying business, the business of law, or professional services more generally"--Publisher.
Includes bibliographical references and index.
Keywords: Organizational change; Employee motivation; Personnel management